Cell-free DNA: a metabolic byproduct with diagnostic and prognostic potential in rheumatic disorders - Liu, Fancheng; Su, Yazhen; Liu, Xinling; Zhao, Li; Wu, Zewen; Liu, Yang; Zhang, Liyun (Frontiers in Pharmacology, 2025)
The release of intracellular DNA into the extracellular area occurs via two pathways: cell death and active secretion by cells. The DNA, which is free in the extracellular space, is commonly known as Cell-Free DNA (cfDNA). In healthy people, the levels of cfDNA in the circulation are notably minimal. Within a healthy organism, cfDNA undergoes swift elimination and filtration upon release, ensuring a persistently low concentration in the bloodstream. Conversely, individuals suffering from diverse illnesses like stroke, trauma, myocardial infarction, and various cancers show markedly higher levels of cfDNA in their blood plasma or serum. Further research has shown that cfDNA is associated with a wide range of human diseases and may have a feedback relationship with inflammation, potentially serving as a non-invasive, accurate, sensitive, and rapid biomarker for clinical applications in disease differential diagnosis, activity monitoring, and prognosis assessment. Studies dating back to the 1970s have indicated elevated cfDNA concentrations in SLE. Currently, increased levels of cfDNA are noted in a range of rheumatic disorders. Inflammatory damage in patients with rheumatic diseases promotes the release of cfDNA, while potential abnormalities in cfDNA metabolism further increase its levels. Elevated concentrations of cfDNA are recognized by DNA receptors, initiating immune-inflammatory reactions which subsequently accelerate the progression of disease. Reducing excess cfDNA may help improve inflammation. Additionally, several trials have demonstrated a correlation between cfDNA concentrations and the activity of rheumatic diseases, indicating the potential of cfDNA, a novel marker for inflammation, in conjunction with C-creative protein (CRP), Erythrocyte Sedimentation Rate (ESR) to monitor disease activity in rheumatic conditions. This paper provides an overview of cfDNA and summarizes current research advancements in cfDNA in rheumatic diseases, aiming to offer new perspectives for researchers.